History Learning for Students Through Lubuklinggau Local History Study Tour Activities - Susilo, Agus; Sari, Ratna Wulan; Satinem, Yohana (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2024)
The problem that arises in learning History today is how to make History material more interesting. The current learning system is still considered conventional which causes the belief that learning History is less active. The purpose of this research is learning History in students through Lubuklinggau local history study tour activities. The method of implementation in the current learning process of History is using qualitative descriptive method. In this descriptive method, the researcher tries to describe the research carried out with appropriate reference sources. The results and discussion include: History learning in Higher Education is that current History learning continues to be improved. History learning is not only carried out by discussing textbooks, but is made as interesting as possible. History lecturers have a big responsibility in realizing this. Then the Lubuklinggau local history study tour is a tourist study activity carried out by lecturers together with students to visit historical places in Lubuklinggau City. This activity will add insight and essential knowledge for students. The History learning system will be more colorful and create a spirit of learning History for students. The conclusion is that the improvement of the History learning system can be done by lecturers with local history study tours. This activity can increase knowledge and provide valuable experience for students related to learning History, local culture and traditions. Of course, apart from being a medium for learning History directly, it is also a promotional medium in introducing valuable heritage to the wider community.